1976
DOI: 10.3181/00379727-152-39388
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Consequences of Vitamin Deficiencies on Background Plaque-Forming Cells in Rats

Abstract: The detrimental effects of specific vitamindeficiency states on the immune response have been known for some time (1). The pronounced impairment of the immune system has been well documented in both pyridoxine-and pantothenic acid-deficient rats (1). Defects in immune capacity in such deficient animals can be attributed neither to general inanition nor to impaired reticuloendothelial function in antigen distribution, but rather to decreased numbers of hemolytic antibody-producing cells as measured in plaque-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Experimental procedures inducing deficiency in PA by means of diets induced a marked delay in wound healing [5] and histological modification of the cicatricial granulated tissue [5,7]. Furthermore, this de-ficiency caused a decreased resistance to infection in experimental animals [9]. On the opposite, recent studies have revealed that a pre-and post-operative PA supplementation increased aponeurosis, skin strength, and fibroblast content of the scar during the phase of cell proliferation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental procedures inducing deficiency in PA by means of diets induced a marked delay in wound healing [5] and histological modification of the cicatricial granulated tissue [5,7]. Furthermore, this de-ficiency caused a decreased resistance to infection in experimental animals [9]. On the opposite, recent studies have revealed that a pre-and post-operative PA supplementation increased aponeurosis, skin strength, and fibroblast content of the scar during the phase of cell proliferation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Such cells may reflect the following: (1) prior exposure to cross-reacting antigens; (2) spontaneously arising clones of immunocompetent cells of restricted specificity, and (3) B cell activity generated in response to immunoregulatory cells belonging to either T or B lymphocyte populations [10]. Although autoreactive background PFC have been described [10,11], their etiology is also a mystery. Further insight into their origins might help to pro vide some understanding of why a small percentage of Rh-negative women appear to be sensitized as primagravidas to their Rh-positive fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of background PFC to various erythrocyte targets at various stages in development of human and other species has been reported only sporadically [3,4,[8][9][10][11]. The biological significance of back ground PFC is unknown [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they observed that the granulation tissue which was produced under such conditions was much less dense and more vascular and cellular than that found in control animals. In another study, deficiencies of the B‐complex vitamins pyridoxine, pantothenic acid, and folic acid caused a decrease in resistance to infection in experimental animals. Apparently, antibody formation and some white cell functions are impaired when these vitamins are deficient.…”
Section: The Role Of Vitaminsmentioning
confidence: 96%